Killer and Guest: A Brief Analysis of the Semantic Horizon of goghna- through Aṣṭādhyāyī and Ṛgveda - Borghero, Anita (Folia Orientalia, 2025)
Within the section devoted to the description of kṛt suffixes, rule A 3.4.73 dāśagoghnau sampradāne teaches how to correctly interpret the terms dāśa- and goghna-, two deverbal nominal stems respectively derived from dāś- ‘to give’ and go- ‘cow’ + han- ‘to kill’. As taught by the constraint of this sūtra, which is sampradāne, these terms denote recipients and not agents as might be expected. In other words, in the language described by Pāṇini, a dāśa- is ‘the one to whom something is given’, while a goghna- is ‘someone for whom a cow is killed’, i.e., a guest. In the main frame of comparative research between Pāṇini and the language of the Vedas and with the specific aim of going deeper into the linguistic datum documented by A 3.4.73, this paper focuses on the technical and semantical analysis of the term goghna- with a special attention to the Ṛgveda. Finally, some suggestions about the cultural implications of the semantic switch reported by the Aṣṭādhyāyī will be considered in the conclusions.